Receptor for advanced glycation end-products (RAGE) provides a link between genetic susceptibility and environmental factors in type 1 diabetes - Forbes, Josephine M.; Söderlund, J.; Yap, F. Y. T.; Knip, M.; Andrikopoulos, S.; Ilonen, J.; Simell, O.; Veijola, R.; Sourris, K. C.; Coughlan, M. T.; Forsblom, C.; Slattery, R.; et al. (Diabetologia, 2011)
This group of studies examines human genetic susceptibility conferred by the receptor for advanced glycation end-products (RAGE) in type 1 diabetes and investigates how this may interact with a western environment.
Ein Erratum zu diesem Artikel wurde am 13. April 2011 veröffentlicht
Gesehen am 08.02.2023